Galectin-9 binding to HLA-DR in dendritic cells controls immune synapse formation and T cell proliferation - Andrea Rodgers-Furones; Thijs Brands; Guusje van Gameren; Mirane Florencio-Zabaleta; Mayukha Bathini; Sandra Delgado; Zacharias Wijfjes; Kristina Fedorova; René Classens; Lona Kroese; Martijn Verdoes; Guido van Mierlo; et al. (Proceedings of the National Academy of Sciences, 2025)
To initiate T cell–mediated immunity, dendritic cells (DCs) present antigens to T cells through the establishment of an immune synapse (IS). While events behind IS formation in T cells are well understood, the organization of IS components at the DC membrane remains ill-defined. Galectins modulate immune responses via glycan-(in)dependent interactions but the molecular mechanisms underlying their function in DC–mediated T cell activation, are poorly described. Here, we demonstrate that intracellular galectin-9 (gal9) in DCs is required for CD4 + T cell activation through its interaction with the HLA-DR alpha- and beta- cytoplasmic domains, as supported by coimmunoprecipitation, mass spectrometry, and NMR analyses. Live-cell imaging revealed gal9-depleted DCs fail to establish stable ISs with T cells, reducing T cell activation and proliferation. Notably, HLA-DR membrane lateral mobility and recruitment to the IS was diminished in DCs lacking gal9. Conditional gal9 knockout in DCs led to enhanced tumor growth in vivo, underscoring a role for gal9 in T cell–dependent antitumor immunity. Collectively, this study reports gal9-mediated HLA-DR organization at the DC synapse, uncovering a mechanism through which intracellular galectins coordinate immune receptor positioning to enhance CD4 + T cell activation.